2019
DOI: 10.1021/acs.bioconjchem.9b00065
|View full text |Cite
|
Sign up to set email alerts
|

Installation of Trimethyllysine Analogs on Intact Histones via Cysteine Alkylation

Abstract: Site-specific incorporation of post-translationally modified amino acids into proteins, including histones, has been a subject of great interest for chemical and biochemical communities. Here, we describe a site-specific incorporation of structurally simplest trimethyllysine analogs into position 4 of the intact histone H3 protein. An efficient alkylation of cysteine 4 of the recombinantly expressed histone H3 provides a panel of trimethyllysine analogs that differ in charge, charge density, sterics, and chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…At present, however, it is not clear how well do unnatural cysteine-derived amino acids resemble natural unmodified and posttranslationally modified amino acids. 20,23,24,26 There are some conflicting quantitative data on whether epigenetic reader proteins recognize the cysteine-derived γ-trimethylthialysine (KCme3) and trimethyllysine (Kme3) equally well, [27][28][29] while KCme3 appears to be a poor substrate for histone lysine demethylases. 30 Enzymatic assays using [ 3 H-Me]-SAM showed that histones bearing γ-thialysine (KC), the cysteine-derived γ-thialysine analog, underwent the SUV39H1 methyltransferase-catalyzed methylation reaction.…”
Section: And Iii)mentioning
confidence: 99%
“…At present, however, it is not clear how well do unnatural cysteine-derived amino acids resemble natural unmodified and posttranslationally modified amino acids. 20,23,24,26 There are some conflicting quantitative data on whether epigenetic reader proteins recognize the cysteine-derived γ-trimethylthialysine (KCme3) and trimethyllysine (Kme3) equally well, [27][28][29] while KCme3 appears to be a poor substrate for histone lysine demethylases. 30 Enzymatic assays using [ 3 H-Me]-SAM showed that histones bearing γ-thialysine (KC), the cysteine-derived γ-thialysine analog, underwent the SUV39H1 methyltransferase-catalyzed methylation reaction.…”
Section: And Iii)mentioning
confidence: 99%
“…Despite different folding patterns, these reader proteins have a common feature as they all possess electron-rich aromatic cages, most often comprised of 1-4 side chains of Phe, Tyr and Trp, although some cages also include the negatively charged Asp or Glu residues 13,14 . Comparative binding studies between trimethyllysine and its neutral carba analogue led to the conclusion that the recognition of the positively charged trimethyllysine by the aromatic cage containing readers is predominantly driven by a combination of favourable cation-π interactions and the release of high-energy water molecules located inside the aromatic cages [15][16][17] .…”
mentioning
confidence: 99%
“…Cysteine residues contain a reactive thiol group, rendering them very amenable to conjugation chemistries (Figure 16, top). Fortunately, histones H2A, H2B, and H4 do not contain any native Cys residues, and H3 contains just one or two Cys residues, depending on isoform, that can be mutated to Ala or Ser with no functional consequences [387] . Together, this allows any histone residue to be mutated to a Cys for site‐specific labelling.…”
Section: Synthetic Histonesmentioning
confidence: 99%
“…Cysteine conjugations have proved useful for installing PTMs and PTM analogues, particularly those of lysine in histones [388] . In recent years, a wide variety of trimethyllysine analogues have been installed in H3 through Cys alkylation [387] . Hydrazide analogues of acetyl‐, hydroxyisobutyryl‐, and ubiquityllysine have also been installed at sites 56 and 122 in H3 by Cys mutation, showing that hydroxyisobutyrylated and ubiquitinylated K56 increase DNA unwrapping, and at K122, all three PTMs destabilize the nucleosome [389] .…”
Section: Synthetic Histonesmentioning
confidence: 99%